Analysis of crosstalk signals in a cylindrical layered volume conductor – Influence of the anatomy, detection system and physical properties of the tissues - Hanekom, Tania (University of Pretoria, 2013)
Dissertation (MEng(Bio-Engineering))--University of Pretoria, 2007.